UHPLC Analysis of Phenolic Compounds from Phanera strychnifolia Leaf Extracts, and Their Alpha-glucosidase and Alpha-Amylase Inhibitory Activities Supported by Molecular Docking - Kongkiatpaiboon, Sumet; Tayana, Ngampuk; Seaho, Boonwiset; Schinnerl, Johann; Duangdee, Nongnaphat; Inthakusol, Wichayasith; Mudjupa, Chawannuch; Chewchinda, Savita (Trends in Sciences, 2026)
Phanera strychnifolia is a traditional medicinal plant showing remarkable antihyperglycemic activity. To develop as a phytopharmaceutical product for Diabetes, an in-depth investigation of the α-glucosidase and α-amylase inhibitory activities of the main constituents was conducted. The developed UHPLC method was validated for qualitative and quantitative analyses of the major constituents gallic acid (1), trilobatin (2), yanangdaengin (3), and phloretin (4). The performed stress tests provide information about storage conditions and about the stabilities of these compounds under various conditions. The optimized extraction with ethanol/water (1:1, v/v) gave the highest yield of gallic acid (1), and the dihydrochalcones trilobatin (2), yanangdaengin (3), and phloretin (4). Yanangdaengin (3) exhibited potent α-glucosidase inhibitory activity (IC50 of 10.42 µM), which was about 30 times higher active than the commercial drug acarbose (IC50 of 329.09 µM). This result was also confirmed by computerized molecular docking. Our work confirms the suitability of hydrophilic leaf extracts from P. strychnifolia as a potential herbal medicine for the treatment of postprandial hyperglycemia and provides valuable information for the phytopharmaceutical development of this plant. HIGHLIGHTS Alpha-glucosidase and alpha-amylase inhibitory activities from Phanera strychnifolia leaf extracts were studied. The bioactive compounds were confirmed with molecular docking. Yanangdaengin (3) exhibited potent α-glucosidase inhibitory activity (IC50 of 10.42 µM), which was about 30 times more active than the commercial drug acarbose (IC50 of 329.09 µM). The UHPLC method for qualitative and quantitative analyses of gallic acid (1), trilobatin (2), yanangdaengin (3), and phloretin (4), the major constituents in Phanera strychnifolia leaf extract was developed and validated. A suitable extraction method of this plant was developed and optimized. Extraction with ethanol/water (1:1, v/v) gave the highest yield of gallic acid (1), and the dihydrochalcones trilobatin (2), yanangdaengin (3), and phloretin (4). GRAPHICAL ABSTRACT